(untitled) (Studia Prawnicze / The Legal Studies, 1985)
The article deals with the influence of the philosophical Lwów-Warsaw school on the Polish theory of law. It has been pointed to the fact that the school exterted influence both on general features of the Polish theory of law as well as on the way of solving certain problems by Polish theoreticians of law. As far as general problems are concerned, intensive research on the so-called logic linguistic plane is undoubtedly connected with logical works by philosophers from Warsaw school. Detailed problems are illustrated in the article by works by J. Zajkowski (connection with T. Kotarbiński’s theory), S. Frydman (application of radical conventionalism in the theory of dogmatics of law), W. Lang (problems connected with the analysis of the notion of valid law) and J. Wróblewski (application of the theory of language of K. Ajdukiewicz in the semantics of norms).